Association of CSN1S1 gene polymorphism on milk components of the Indonesian local PE cross-dairy goats. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to identify Casein Alpha S1 (CSN1S1) gene polymorphism as a biomarker selection for improving the milk quality of Indonesian local PE cross-dairy goats. Materials and Methods: The study utilized 65 does to identify single nucleotide polymorphisms (SNPs) on the target base fragment g.10094 gm.10200 of the CSN1S1 gene. Milk components (MCs) were analyzed using lactoscan and SNPs were identified using Sanger sequencing. Allele and genotype frequencies of the SNPs were determined by MEGA10 and PopGen32 programs. A general linear model was applied to examine the association between each SNP and the content (%) or daily yield (gm/day) of each of the MCs. Results: Eight SNPs were identified, with seven exhibiting dominant homozygous genotype references with genotype frequencies ranging from 0.77 to 0.95. SNP g.10098_C > G significantly affected (p < 0.05) the daily yield (gm/day) of MCs, but not for TS. The CC does, compared to the GC ones, produce higher yields (gm/day) of protein, fat, lactose, and SNF by 36.2%–39.8%. SNP g.10181_T > A had a significant effect (p < 0.05) on the content (%) of all MCs. The AT does, over the AA and TT ones, yield higher MCs by 3.63%–13.07% and 1.85%–10.68%, respectively. Conclusion: The findings suggest that SNP g.10098_C > G and g.10181_T > A of the CSN1S1 gene may serve as potential biomarkers for selective breeding to enhance milk quality in the local PE cross-dairy goats.J. Adv. Vet. Anim. Res., 12(1): 222–230, March 2025http://doi.org/10.5455/javar.2025.l889